The Construction – Technological Research of Vertical Kiln Located in Former Nobility Malt Plant in Želetava - Libor Doležal; Milan Starec (Kvasný průmysl, 2015)
In the sixties of the 16th century in the object, so called Starý Hrad (Old castle), had been constructed the brewery with the malt plant. In the year 1867 had been constructed new brewery, former brewery with a malt plant has been reconstructed only for malt production, the company Noback & Fritze had constructed an vertical air kiln. In the year 1908 the company Novak & Jahn had the kiln thoroughly reconstructed. The unique technological equipment of the kiln has been preserved until today. Detailed survey of the kiln should be used to understand its functions, conservation and preservation of this technical monument and should be a guide for public performances of kiln.